Plumbagin inhibits fungal growth, HMGB1/LOX-1 pathway and inflammatory factors in A. fumigatus keratitis - Cong, Fan; Gu, Lingwen; Lin, Jing; Liu, Guibo; Wang, Qian; Zhang, Lina; Chi, Menghui; Xu, Qiang; Zhao, Guiqiu; Li, Cui (Frontiers in Microbiology, 2024)
To investigate the anti-inflammatory and antifungal effects of plumbagin (PL) in Aspergillus fumigatus (A. fumigatus) keratitis, the minimum inhibitory concentration (MIC), time-killing curve, spore adhesion, crystal violet staining, calcium fluoride white staining, and Propidium Iodide (PI) staining were employed to assess the antifungal activity of PL in vitro against A. fumigatus. The cytotoxicity of PL was assessed using the Cell Counting Kit-8 (CCK8). The impact of PL on the expression of HMGB1, LOX-1, TNF-α, IL-1β, IL-6, IL-10 and ROS in A. fumigatus keratitis was investigated using RT-PCR, ELISA, Western blot, and Reactive oxygen species (ROS) assay. The therapeutic efficacy of PL against A. fumigatus keratitis was assessed through clinical scoring, plate counting, Immunofluorescence and Hematoxylin-Eosin (HE) staining. Finally, we found that PL inhibited the growth, spore adhesion, and biofilm formation of A. fumigatus and disrupted the integrity of its cell membrane and cell wall. PL decreased IL-6, TNF-α, and IL-1β levels while increasing IL-10 expression in fungi-infected mice corneas and peritoneal macrophages. Additionally, PL significantly attenuated the HMGB1/LOX-1 pathway while reversing the promoting effect of Boxb (an HMGB1 agonist) on HMGB1/LOX-1. Moreover, PL decreased the level of ROS. In vivo, clinical scores, neutrophil recruitment, and fungal burden were all significantly reduced in infected corneas treated with PL. In summary, the inflammatory process can be inhibited by PL through the regulation of the HMGB-1/LOX-1 pathway. Simultaneously, PL can exert antifungal effects by limiting fungal spore adhesion and biofilm formation, as well as causing destruction of cell membranes and walls.